THE RELATIONSHIP BETWEEN TEACHER PROFESSIONAL COMPETENCE, MADRASAH CULTURE, AND WORK COMMITMENT AND TEACHER JOB SATISFACTION AT STATE MADRASAH TSANAWIYAH IN THE RIAU ISLANDS PROVINCE - Andika Setiawan; Risnita; Kemas Imron Rosadi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
This study aims to analyze the relationship between teachers’ professional competence, madrasah culture, and work commitment toward teacher job satisfaction in State Madrasah Tsanawiyah (MTsN) across the Riau Islands Province. The research population consists of teachers from 13 madrasahs, with the sample selected through cluster sampling representing three regional zones: east, central, and west. A total of 90 teachers were sampled, comprising 30 teachers for instrument try-out and 60 teachers as the primary research participants. Using a quantitative method with a correlational approach, this study examines the individual and simultaneous contributions of each variable.The findings indicate that teachers’ professional competence which includes mastery of subject matter, pedagogical skills, and managerial abilities enhances job satisfaction by strengthening confidence and task effectiveness. A strong and consistent madrasah culture characterized by discipline, collaboration, religiosity, and a harmonious work climate also contributes significantly to teacher job satisfaction by fostering a supportive institutional environment. Teacher work commitment likewise plays an important role, as highly dedicated and loyal teachers tend to experience greater job satisfaction. Collectively, the three variables demonstrate a significant combined relationship, reinforcing the notion that job satisfaction results from the interaction of professional, cultural, and psychological dimensions within educational institutions. These findings highlight the need for strengthening teacher competence, institutional culture, and work commitment to develop motivated and high-performing educators